THE INFLUENCE OF SHARIA BANK ASSETS ON POVERTY LEVELS IN INDONESIA FOR THE 2015-2022 PERIOD - Ulfah, Muthia; Arifah, Lidyana (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Poverty is one of the main problems in Indonesia. On the other side, strengthening the financial sector is one of the solutions for poverty alleviation, especially in the banking sector. This research was conducted to see the effect of Islamic bank assets on poverty. For this reason, this study used a quantitative method with simple linear regression to analyze data. The data used is secondary data, the data on Islamic bank assets, and the data on poverty rates in Indonesia for the 2015-2022 period. The results of the regression test show that the growth of Islamic bank assets has a negative but not significant effect on poverty with a coefficient of 0.000935